Análise da qualidade de vida na cidade de Araçatuba (São Paulo): uma proposta metodológica com a utilização de sistemas de informação geográfica (sig) - Marcio Fernando Gomes; Deise Regina Elias Queiroz (Confins)
The aim of this paper is to present a methodology to analyze the quality of urban life through the spatial distribution of indicators related to infrastructure, public services and environmental quality using Geographic Information Systems (GIS). For the evaluation of the quality of urban life the following indicators were considered: water supply, sewage, garbage collection, road paving, health facilities, educational institutions, public transport, recreation areas, free flood areas and vegetation cover. This study was developed in the city of Araçatuba (São Paulo) and the results showed that, in general, the quality of life index tends to be higher in sectors located near the central area, is gradually falling toward the periphery and reaches the worst values in the transition areas between urban and rural areas.